2020
DOI: 10.3390/w12113129
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Composition of Leachate from Active and Non-Operational Municipal Waste Landfills in Poland

Abstract: Leachate formation is one of the many environmental hazards associated with landfilling. The leachate may migrate from the landfill to surface water and groundwater, posing a potential threat to aquatic ecosystems. Moreover, its harmful effect on human health and life has been proven. Due to the risks that landfill leachates may pose, it is necessary to control the state of the environment in their surroundings. The paper presents an example of the application of selected statistical methods (basic statistics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…The studies showed similar level of COD values in leachates from these landfills. It should be noted that the landfills were put into operation at a similar time (1997)(1998)(1999)(2000)(2001) and the results of the investigations may confirm a similar character of the decomposition processes taking place in the deposits of the deposited wastes.All COD values obtained in the conducted studies were within the ranges reported also by other authors (Kjeldsen et al, 2002;Tatsi and Zouboulis, 2002;Wdowczyk and Szymańska-Pulikowska, 2020), confirming that one of the main factors affecting their values is the age of the landfill site (or rather the age of the deposited waste), because with the passage of time the susceptibility of waste to biological and chemical degradation processes decreases.…”
Section: Codsupporting
confidence: 85%
“…The studies showed similar level of COD values in leachates from these landfills. It should be noted that the landfills were put into operation at a similar time (1997)(1998)(1999)(2000)(2001) and the results of the investigations may confirm a similar character of the decomposition processes taking place in the deposits of the deposited wastes.All COD values obtained in the conducted studies were within the ranges reported also by other authors (Kjeldsen et al, 2002;Tatsi and Zouboulis, 2002;Wdowczyk and Szymańska-Pulikowska, 2020), confirming that one of the main factors affecting their values is the age of the landfill site (or rather the age of the deposited waste), because with the passage of time the susceptibility of waste to biological and chemical degradation processes decreases.…”
Section: Codsupporting
confidence: 85%
“…In the raw leachate samples from the tested municipal landfill, pH peaked at 9.0 with an average of 8.2. This indicates that the leachate comes from a mature landfill, which has been in use for over ten years (Nájera-Aguilar et al, 2019) and is in the methanogenic phase (Wdowczyk and Szymańska-Pulikowska 2019). In turn, low concentrations of Hg at 5 µg/L and Cd at 36 µg/L were recorded in the investigated leachate.…”
Section: Discussionmentioning
confidence: 79%
“…The highest value of TDS was observed in the active landfill in Legnica (7,065 mg/dm 3 ), and the lowest in the landfill in Wrocław (1,690 mg/dm 3 ). The high content of solid solutes is reflected in the high EC values of the leachate (Wdowczyk and Szymańska, 2020). The leachate from the active landfills was characterized by high COD values, much higher than those recorded in the closed facilities.…”
Section: Analysis Of Physicochemical Properties In Raw Leachatementioning
confidence: 94%
“…In recent years, increasingly more studies have shown that the content of heavy metals ceases to be the most serious threat posed by landfill leachate (Christensen et al, 2001;Przydatek, 2019a;Wdowczyk and Szymańska-Pulikowska, 2020). However, studies showing a serious threat of heavy metal contamination of soil, surface water and groundwater by landfill leachate can still be found.…”
Section: Analysis Of Physicochemical Properties In Raw Leachatementioning
confidence: 99%